THE IMPLEMENTATION OF CRITICAL THINKING SKILLS IN TEACHING ENGLISH AT VOCATIONAL SCHOOLS IN MAJENE REGENCY - Lina Fitriani; Iskandar; Nur Aeni (Bahasa Inggris Program Sarjana Terapan, Universitas Negeri Makassar, 2024)
This research focused on understanding various aspects related to the implementation of critical thinking skills among English teachers in vocational schools in Majene, Sulawesi Barat. The specific objectives were to investigate: (1) How English teachers prepare to implement critical thinking skill, involving diagnostic tests and lesson plan development. (2) The actual integration and effectiveness of critical thinking skills in English instruction at these vocational schools. (3) The methods used by teachers to evaluate students' critical thinking abilities, encompassing attitude, knowledge, and skill assessments. The study utilized a descriptive qualitative method, involving observation, interviews, and documentation with four certified English teachers from selected schools. The findings highlighted the multi-faceted nature of preparing, implementing, evaluating related to critical thinking skills in the vocational school. The result of data analysis revealed that The English teacher's preparation for integrating critical thinking skills involves two essential stages: conducting diagnostic tests to assess fundamental abilities and learning styles, and designing a comprehensive lesson plan. Throughout the learning process, critical thinking is actively applied, beginning with trigger questions in introductory activities, followed by problem-solving and group discussions in core activities, and concluding with students providing conclusions or constructive criticism. The assessment of students' critical thinking skills is conducted through Higher Order Thinking Skills (HOTS) questions, encompassing both written and oral tests.